Service quality assessment in a Greek higher education institute - Zafiropoulos, Costas; Vrana, Vasiliki (Journal of Business Economics and Management, 2008)
Education service quality, even though it has become a major issue in higher education worldwide, in Greece it has gained attention only in the last few years. The paper analyzes how students and staff shape opinion about quality of education in a HE institute in Greece. This is one of the few analyses of the perceptions about quality of educational services, viewed both by students and staff of Higher Education Institute in Greece. The study uses the SERVQUAL instrument, adjusted in the educational context. It finds the gaps within students’ and staff’s attitudes and reveals possible differences between students’ and staff’s views. Gaps exist among some students’ attitudes regarding perceived and expected quality. Staff presents greater gaps than students in every SERVQUAL dimension. Although staff’s scores about perceived and expected quality differentiate significantly from students’ scores, no statistically significant difference exists regarding the final SERVQUAL scores. The SERVQUAL instrument presents high reliability indices, however its validity is questioned. The issue has important strategic and managerial implications because it relates to the ability of the institution to bridge staff’s and student’s attitudes. Although SERVQUAL presents some limitations regarding applicability it still may be used as a complementary research instrument for assessing service quality. In the educational context SERVQUAL can be used to reveal differentiation among views of the key stakeholders, such as students and staff. Managers should take steps to ensure that both parts form a realistic view of the educational process. First published online: 14 Oct 2010